Electrochemical and spectroelectrochemical characterization of meso-tetra-alkyl porphyrins - Paliteiro, Carlos (2005)
A series of three meso-tetra-alkyl porphyrins (H2TAPs) were synthesised and their electrochemical properties were studied in dichloromethane containing either tetra-butyl ammonium perclorate (TBAP) or tetra-butyl ammonium hexafluorophosphate TBA(PF6) as supporting electrolyte (SE) by cyclic voltammetry and in situ UV/vis spectroelectrochemistry. Values of E1/2 for the recorded four redox processes of these porphyrins and of the meso-tetra-phenyl porphyrin (H2TPP) on glassy carbon and platinum were measured and compared. The redox data collected on the first oxidation and the first reduction processes predict that the value of [Delta](LUMO - HOMO) for the H2TAPs is lower than for meso-tetra-phenyl porphyrin and, therefore, that the first Q band of the electronic spectra of the H2TAPs is red shifted relatively to the same band in the spectrum of H2TPP; this shift was indeed found. The second oxidation process of the H2TAPs is influenced by the supporting electrolyte used and the dication then formed is consumed by an irreversible chemical reaction. The species produced in this reaction is irreversibly reduced at a considerably lower potential. The electrochemical and spectroelectrochemical data collected are consistent with the occurrence of structural distortion in the macrocycle rings of the H2TAPs.